1996
DOI: 10.1093/jnci/88.8.510
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of the Inactivated X Chromosome in Ovarian Epithelial Tumor Development

Abstract: LOH at multiple loci is associated with the development of ovarian carcinomas but not with the development of cystadenomas and LMP tumors. However, the integrity of a locus in chromosome Xq that possibly escapes X-chromosome inactivation is important for the control of LMP tumor development. The fact that this locus does not appear to be involved in the genesis of low-grade carcinomas suggests that LMP tumors are not precursors of such carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 0 publications
5
44
1
1
Order By: Relevance
“…This conclusion is also supported by recent data from our laboratory (Cheng et al, 1996). The available evidence therefore supports the notion that LMP tumours are mechanistically more complex than cystadenomas and strongly argues in favour of maintaining the distinction between these two variants of ovarian epithelial tumours, in spite of the fact that they often show similar clinical behaviour.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This conclusion is also supported by recent data from our laboratory (Cheng et al, 1996). The available evidence therefore supports the notion that LMP tumours are mechanistically more complex than cystadenomas and strongly argues in favour of maintaining the distinction between these two variants of ovarian epithelial tumours, in spite of the fact that they often show similar clinical behaviour.…”
Section: Discussionsupporting
confidence: 86%
“…Although such changes are clearly associated with the malignant phenotype in a large number of different tumour types (Gama-Sosa et al, 1983), they are also found in some benign neoplasms such as colorectal polyps (Goelz et al, 1985;Feinberg et al, 1988). Ovarian epithelial tumours are a good model to address this question because there are two well-defined subtypes of these tumours that do not fully express the malignant phenotype (Cheng et al, 1996) and can therefore be regarded as different early stages of malignant transformation. The results of our experiments clearly show that DNA methylation changes are present in both, ovarian LMP tumours and carcinomas, lending further support to the idea advanced by Goelz et al (1985) that such changes are early events in malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…19 The LOH frequency on Xq has been reported to be 50% and that on all other chromosomes is less than 10% in LMP. 20 In the present study, LOH of the AR locus was observed in 50% of serous OC cases but was not found in other types of ovarian tumors. Moreover, mucinous LMP accounted for 84% of our cases, whereas 26% of cases were mucinous LMP in the study of Cheng et al 20 This discrepancy in LOH frequency may be attributed to the different incidence of each histologic subtype.…”
Section: Loh Analysis In Ovarian Tissues From Different Lesionscontrasting
confidence: 54%
“…Critical to this examination is the role that tumor suppressor genes play in the development of ovarian cancer. Cytogenetic and molecular studies have attempted to pinpoint the sites of alteration leading to the development of this disease by noting alterations at chromosome 3p (Tanaka et al, 1989), 5q (Weitzel et al, 1994), 6q (Rodabaugh et al, 1995b;Lee et al, 1990;Foulkes et al, 1993b;Sato et al, 1991), 9p (Rodabaugh et al, 1995a), 11 (Eccles et al, 1992a;Davis et al, 1996;Lee et al, 1990;Gallion et al, 1990Gallion et al, , 1992, 13 (Yang-Feng et al, 1992Sato et al, 1991;Gallion et al, 1992;Dodson et al, 1993), 17 (Wertheim et al, 1994;Foulkes et al, 1993a;Eccles et al, 1992b;Tangir et al, 1996;Pieretti et al, 1995;Lee et al, 1990;Cliby et al, 1993;Yang-Feng et al, 1993;Gallion et al, 1992;Dodson et al, 1993), 19 (Sato et al, 1991), 22 (Bryan et al, 1996), and X (Yang-Feng et al, 1992;Cheng et al, 1996).…”
Section: Introductionmentioning
confidence: 99%